ROOTING OF FIG TREE APICAL CUTTINGS ‘ROXO DE VALINHOS’ IN PLANTS WITH LOPPING SYSTEM - HOFSTAETTER, Jhuan Kaster; PIO, Rafael; CAMPAGNOLO, Marcelo Angelo; DALASTRA, Idiana Marina; CURI, Paula Nogueira; MOURA, Pedro Henrique Abreu (Scientia Agraria, 2010)
The only cultivar of fig tree for commercial purposes in Brazil is the ‘Roxo de Valinhos’, propagated by stem cutting. Trying to increase the efficiency of the tree figs for the production of green figs, was developed a conduction system with lopping realization. Therefore, the present work aims to verify the potential of rooting of the apical cuttings from the fig tree collected from plants with different amounts of looping. To this end, we used apical cuttings of plants conducted with six and twelve productive branches and have suffered none, one or two lopping, which were or were not treated with a 2000 mg dm-3 acid indolbutiric (IBA) for 10 seconds. All cuttings were collected in July. These were patterned with 20 cm length and 10 mm diameter and buried ¾ of their length in sand moistened. After 60 days, concluded that cuttings collected from plants with lopping favored an increase in the percentage of roots and sprouts; the application of IBA increased the roots emission and sprouts.